2006
DOI: 10.1902/jop.2006.050051
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal and Hematological Characteristics Associated With Aggressive Periodontitis, Juvenile Idiopathic Arthritis, and Rheumatoid Arthritis

Abstract: Young adults with RA may develop periodontal destruction, and these patients require professional attention. Both differences and similarities in periodontal and hematological variables were seen in individuals with periodontitis, JIA, and RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
123
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(143 citation statements)
references
References 40 publications
(53 reference statements)
13
123
1
6
Order By: Relevance
“…RA is 4 times more common in patients with periodontitis than in the normal population (43), and higher levels of antibodies to P gingivalis (44), as well as a higher prevalence of advanced forms of periodontal destruction, have also been reported in patients with RA compared with control subjects. Finally, both rheumatoid factor production and anti-CCP antibody production have been associated with periodontal disease (41,45).…”
Section: Discussionmentioning
confidence: 99%
“…RA is 4 times more common in patients with periodontitis than in the normal population (43), and higher levels of antibodies to P gingivalis (44), as well as a higher prevalence of advanced forms of periodontal destruction, have also been reported in patients with RA compared with control subjects. Finally, both rheumatoid factor production and anti-CCP antibody production have been associated with periodontal disease (41,45).…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis may be a risk factor for arthritis development, as it enhances the severity of rheumatoid arthritis [14,15]. Furthermore, reports have emerged, which suggest that reduction of extra-synovial chronic inflammation, associated with periodontal treatment, may have a beneficial effect on established rheumatoid arthritis [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Australia, America, Europe and Africa have shown that RA patients have more prevalent and severe periodontitis than non-RA controls when controlling for important confounders like dental plaque, age, sex and smoking [2][3][4][5][6][7][8][9] . Studies in Sweden, Brazil, USA, Turkey, and Japan, however, did not find a higher prevalence and severity of periodontitis in RA patients [10][11][12][13][14] .…”
mentioning
confidence: 99%